2021
DOI: 10.1101/2021.02.20.431155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired local intrinsic immunity to SARS-CoV-2 infection in severe COVID-19

Abstract: Infection with SARS-CoV-2, the virus that causes COVID-19, can lead to severe lower respiratory illness including pneumonia and acute respiratory distress syndrome, which can result in profound morbidity and mortality. However, many infected individuals are either asymptomatic or have isolated upper respiratory symptoms, which suggests that the upper airways represent the initial site of viral infection, and that some individuals are able to largely constrain viral pathology to the nasal and oropharyngeal tiss… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 129 publications
(139 reference statements)
6
25
0
2
Order By: Relevance
“…Recent work on the host response to SARS-CoV-2 in the airway epithelium or model cell lines has shown that SARS-CoV-2 can trigger IFN and ISG expression via the viral RNA sensor MDA5, albeit with delayed kinetics, but that this response in some cases was ineffective at curtailing viral replication; furthermore, while pretreatment with exogenous IFN blocked SARS-CoV-2 infection, IFN was much less effective if added after the infection was established ( Yin et al, 2021 ; Rebendenne et al, 2021 ; Hsin et al, 2021 Preprint ). Single-cell analysis of epithelial cells from the nasopharynx of COVID-19 patients showed ISG induction in epithelial cells primarily from patients with mild-to-moderate disease, but not severe disease, consistent with the observation that patients with severe disease are more likely to have genetic or acquired deficiencies in IFN signaling pathways ( Ziegler et al, 2021 Preprint ). Together, these findings indicate that epithelial cells are capable of mounting an IFN response to SARS-CoV-2 but that the timing and magnitude of the IFN response relative to viral replication may be critical for determining the course of infection.…”
Section: Introductionsupporting
confidence: 73%
“…Recent work on the host response to SARS-CoV-2 in the airway epithelium or model cell lines has shown that SARS-CoV-2 can trigger IFN and ISG expression via the viral RNA sensor MDA5, albeit with delayed kinetics, but that this response in some cases was ineffective at curtailing viral replication; furthermore, while pretreatment with exogenous IFN blocked SARS-CoV-2 infection, IFN was much less effective if added after the infection was established ( Yin et al, 2021 ; Rebendenne et al, 2021 ; Hsin et al, 2021 Preprint ). Single-cell analysis of epithelial cells from the nasopharynx of COVID-19 patients showed ISG induction in epithelial cells primarily from patients with mild-to-moderate disease, but not severe disease, consistent with the observation that patients with severe disease are more likely to have genetic or acquired deficiencies in IFN signaling pathways ( Ziegler et al, 2021 Preprint ). Together, these findings indicate that epithelial cells are capable of mounting an IFN response to SARS-CoV-2 but that the timing and magnitude of the IFN response relative to viral replication may be critical for determining the course of infection.…”
Section: Introductionsupporting
confidence: 73%
“…Furthermore, we detect squamous cells with the characteristic expression of SPRR3 and KRT78 . In addition to the unsupervised clustering, we visualised markers ( KRT14 , KRT6A , KRT13 , KRT24 ) that have been associated with “Hillock” cells 44, 49, 50 which seem to align along a distinct differentiation trajectory at the edge of the secretory cluster from basal towards squamous cells ( Extended Data Figure 4a ). Within the ciliated cluster, the differentiation trajectory points from ciliated 1 ( PIFO , OMG ) to ciliated 2 ( CFAP54 , DZIP1L ) cells.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, basal 1 cells are notably reduced. Ciliated and goblet cells contain the highest number of viral reads ( Figure 1f ), most likely leading to cell death 50, 51 . We hypothesize that increased ciliated 1 and goblet 2 cell numbers reflect an ongoing compensatory replacement of these dying cells by their precursors to maintain homeostasis as seen in lower airways upon infection 52, 53 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From nasal surfaces, SARS-CoV-2 can spread locally to the olfactory region and more widely to the oral cavity and lung 1,3 . Accordingly, nasal protection represents an important strategy to limit SARS-CoV-2 infection and transmission 4 . In addition to physical means, e.g., masks, topical administration of a spectrum of virucidal agents to nasal surfaces has been advocated for this purpose, including iodine, metal, and detergent-based molecular entities [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%